A Case of Human Viral Encephalitis Caused by Pseudorabies Virus Infection in China - Yang, HongNa; Han, Hui; Wang, Hao; Cui, Yi; Liu, Han; Ding, ShiFang (Frontiers in Neurology, 2019)
We report a human case of viral encephalitis caused by pseudorabies virus (PRV) in China. A 43-year-old man with no past medical history presented with high-grade fever, headache and tonic-clonic seizures as well as coma. Plain computer tomography (CT) brain imaging showed hypo-density in bilateral basal ganglia, bilateral occipital lobe, bilateral limbic lobe and left thalamic. Next-generation sequencing (NGS) confirmed the presence of PRV in cerebral spinal fluid (CSF). Regular polymerase chain reaction (PCR) was applied to confirm the presence of PRV in the CSF and blood. In addition, serological (immunological) tests were used to further validate the presence of PRV in the peripheral blood. This case suggested that it was possible for PRV to result in central nervous system infection of human and it was necessary for people to increase awareness of self-protection when contacting animals.